2011
DOI: 10.1155/2011/650489
|View full text |Cite
|
Sign up to set email alerts
|

Work, Stress, and Diurnal Bruxism: A Pilot Study among Information Technology Professionals in Bangalore City, India

Abstract: The study assessed the prevalence of diurnal bruxism among information technology (IT) professionals and explored plausible predictors associated with the parafunctional habit. A cross-sectional study was designed and IT professionals were invited to participate. The inclusion criteria composed of participants in service for at least one year, having natural dentition, no history of cervical or facial injury and not undergoing orthodontic therapy. The participants (N = 147) were interviewed by a trained interv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
18
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 16 publications
2
18
0
Order By: Relevance
“…Many studies reported that chronic pain disorders including NPDP have been linked to psychological factors [ 5 , 24 ]. And, a study reported that OPAs are associated with emotional stress induced by social factors [ 25 ]. Vickers et al hypotheses that activation of low-threshold mechanoreceptors by bruxism, which is another form of OPA, may modulate nociception through gate-control mechanisms; bruxism may thus be a potential pain-coping mechanism for AO [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Many studies reported that chronic pain disorders including NPDP have been linked to psychological factors [ 5 , 24 ]. And, a study reported that OPAs are associated with emotional stress induced by social factors [ 25 ]. Vickers et al hypotheses that activation of low-threshold mechanoreceptors by bruxism, which is another form of OPA, may modulate nociception through gate-control mechanisms; bruxism may thus be a potential pain-coping mechanism for AO [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…We found that many patients showed abnormalities in our jaw moving test and recognized PAs while experiencing pain. Previous reports suggested that PAs are associated with emotional stress induced by social factors [ 14 ] and that PAs are recognized as a valid systemic prophylactic reaction in all stress-related diseases [ 13 , 15 ]. Moreover, many studies reported that chronic pain disorders including PDAP have been linked to psychological factors [ 5 , 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…Bruxism is a widespread condition -around 85-90% of the general population grinds their teeth in certain periods of their life, and in 5% of these people, the grinding evolves into a clinical condition [2,3]. The prevalence of bruxism varies greatly from 5% to 96%, which highlights that a varied range of criteria and methods for diagnosing this condition are being used [5,6]. An important aspect to this problem is the age of the patients.…”
Section: Introductionmentioning
confidence: 99%
“…It is being assumed that the peculiarities of bruxism based on the age factor are manifested under the influence of cofactors (alcohol, caffeine, nicotine, etc. ), professional activity, and especially stressful professions [6,12]. Currently, there are no sufficient studies on the peculiarities of SB manifestation based on the age of the patients, while the etiopathogenetic causes of this phenomenon are not yet clear.…”
Section: Introductionmentioning
confidence: 99%